MXene / two-dimensional conductive MOF composite material as well as derivative material, flexible electrode and application thereof

Through the preparation of MXene/two-dimensional conductive MOF composite materials, the problems of poor flexibility and low energy density of existing supercapacitors are solved, and the high electrochemical stability and supercapacitance performance of flexible electrodes in bending state are achieved.

CN119775576APending Publication Date: 2025-04-08ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202411857603.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The poor flexibility and low energy density of existing supercapacitors limit their application in flexible electronic products.

Method used

Using MXene/two-dimensional conductive MOF composite material, a reaction solution containing a single layer of MXene, metal ions, ligands and initiator was used to obtain a MXene@C-MOF composite material with conductive and porous structure, and used as a flexible composite electrode.

Benefits of technology

The excellent electrochemical stability of the flexible electrode in the bending state is achieved, and the supercapacitance performance of the flexible supercapacitor is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775576A_ABST
    Figure CN119775576A_ABST
Patent Text Reader

Abstract

The invention provides an MXene / two-dimensional conductive MOF composite material as well as a derivative material, a flexible electrode and application thereof, and a preparation method of the MXene / two-dimensional conductive MOF composite material comprises the following steps: reacting a reaction solution containing single-layer MXene, metal ions, a ligand and an initiator to obtain the MXene / two-dimensional conductive MOF composite material. According to the MXene / two-dimensional conductive MOF composite material and the derivative material thereof, the original structures of the MXene and the C-MOF are reserved, the excellent performance of the MXene and the C-MOF is achieved, and the super capacitance performance is improved when the MXene / two-dimensional conductive MOF composite material is used as a flexible electrode to be applied to a flexible super capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a MXene / two-dimensional conductive MOF composite material and its derivative materials, flexible electrodes and applications. Background Art

[0002] In the past few decades, portable and flexible electronic products, such as bendable screens, electronic skin, flexible transistors and wearable sensor devices, have developed rapidly. Most of these flexible electronic products require flexible power sources, such as flexible supercapacitors. The two-dimensional material MXene has become an ideal electrode material for flexible and wearable supercapacitors due to its excellent metallic conductivity, adjustable chemical properties, good flexibility and other mechanical properties.

[0003] MXene is a new type of two-dimensional material composed of metal carbides or nitrides. They are usually obtained from three-dimensional layered compounds called MAX phases by chemical exfoliation. The chemical formula of MXene can be expressed as M n+1 X n T x , where M represents a transition metal element (such as Sc, Ti, V, Cr, Zr, Nb, Mo, etc.), X represents carbon and / or nitrogen, and T x Represents the surface end group (such as -O, -OH, -F, etc.).

[0004] MXene materials are widely used as flexible electrode materials due to their excellent flexibility, good electronic conductivity, and excellent mechanical properties, and show broad application prospects in the fields of energy, sensing, catalysis, and biomedicine. MXene can store a large amount of charge through surface Faraday redox reactions and can provide more capacitance than traditional double-layer capacitors. However, two-dimensional MXene sheets are easy to restack during electrode manufacturing, which limits the transport of ions in the electrode and leads to slow kinetics and limited capacitance.

[0005] Metal-organic framework (MOF) is a material self-assembled from organic ligands and metal ions or metal clusters. MOF materials have the advantages of high specific surface area, ultra-high porosity, adjustable pore size, and diverse redox metal centers. Therefore, MOFs have been widely used in many fields, such as gas storage, drug delivery, chemical sensing, catalysis, and energy storage. However, the conductivity of traditional MOFs is not ideal, which limits its application in energy storage fields that require excellent conductivity. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a MXene / two-dimensional conductive MOF composite material and its derivative materials, flexible electrodes and applications, which are used to solve the problems of poor flexibility and low energy density of existing supercapacitors.

[0007] To achieve the above-mentioned object and other related objects, the present invention provides a method for preparing a MXene / two-dimensional conductive MOF composite material, wherein a reaction solution containing a single layer of MXene, metal ions, a ligand and an initiator is reacted to obtain a MXene / two-dimensional conductive MOF composite material (MXene@C-MOF).

[0008] The present invention uses MXene with abundant oxygen-containing functional groups at the end of the surface as a template for the growth of C-MOF, wherein the full name of C-MOF is Conductive Metal-Organic Frameworks; MXene with excellent conductivity is combined with C-MOF with a porous structure to form a layered high ion and electronic conductive network, and C-MOF as an intercalation agent inhibits the interlayer stacking of monolayer MXene, expands the interlayer spacing and increases the specific surface area of ​​the material. The preparation method of the present invention is simple, efficient, mild, and the reagents and instruments used are widely available, and it is expected to achieve mass production; the solvent used in the present invention can be obtained in the laboratory or industrial production, is low-priced, and widely available, and the experimental equipment used is easy to operate, does not require high-power equipment, and the production process is environmentally friendly and energy-saving. The prepared two-dimensional MXene@C-MOF derivative can show excellent electrochemical stability as a flexible composite electrode even in a bent state.

[0009] Preferably, the metal ion is selected from Ni 2+ , Cu 2+ and Fe 3+ One or more of .

[0010] Preferably, the C-MOF of the MXene / two-dimensional conductive MOF composite material (MXene@C-MOF) is one or more of Cu3(HITP)2, Cu3(HHTP)2, Ni3(HITP)2, Fe3(HITP)2 and Ni-BTA.

[0011] Preferably, the ligand is selected from one or more of 1,2,4,5-tetraaminobenzene tetrahydrochloride (BTA·4HCl), 2,3,6,7,10,11-hexaaminotriphenyl hexahydrochloride (HATP·6HCl) and 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP).

[0012] Preferably, the initiator is aqueous ammonia.

[0013] Preferably, the volume ratio of the aqueous ammonia to the reaction solution is (1-5):(50-500), more preferably 3:100.

[0014] Preferably, the metal ions are added in the form of soluble metal salts, and the feeding mass ratio of the monolayer MXene, the ligand and the soluble metal salt is (10~50):(0.5~10):(0.5~10).

[0015] More preferably, the soluble metal salt is selected from one or more of NiCl2·6H2O, CuCl2·2H2O and FeCl3.

[0016] Preferably, the preparation method of the single-layer MXene is: washing the MXene until the pH value of the supernatant is neutral, dispersing it by ultrasonication with water, and continuously introducing an inert gas during the ultrasonication process to obtain a single-layer MXene dispersion.

[0017] Preferably, the preparation method of the MXene is: LiF and HCl are mixed, then added into the MAX phase, and heated and etched under sealed conditions to obtain MXene.

[0018] The present invention also provides a MXene / two-dimensional conductive MOF composite material prepared by the above preparation method.

[0019] The present invention also provides an application of the above MXene / two-dimensional conductive MOF composite material as a flexible electrode in a flexible supercapacitor.

[0020] The present invention also provides a method for preparing a derivative material of a MXene / two-dimensional conductive MOF composite material, wherein the MXene / two-dimensional conductive MOF composite material is annealed under a protective atmosphere to obtain a derivative material of the MXene / two-dimensional conductive MOF composite material.

[0021] The present invention anneals the MXene / two-dimensional conductive MOF composite material to convert the N in the ligand in the C-MOF into MXene nitrogen ends in the form of pyrrolic nitrogen and pyridinic nitrogen, thereby enhancing the activity of the redox reaction.

[0022] Preferably, the annealing temperature is 100-600° C., and the annealing time is 0.5-6 h.

[0023] The present invention also provides a derivative material of the MXene / two-dimensional conductive MOF composite material prepared by the above preparation method.

[0024] The present invention also provides an application of a derivative material of the above-mentioned MXene / two-dimensional conductive MOF composite material as a flexible electrode in a flexible supercapacitor.

[0025] As described above, the present invention has the following beneficial effects: (1) The raw materials are widely available and inexpensive, the preparation method is simple to operate, and the conditions are mild. The morphology of the prepared MXene / two-dimensional conductive MOF composite materials and their derivatives are adjustable, the structure is controllable, the components are evenly distributed, and the nanosheet size is small; (2) The MXene / two-dimensional conductive MOF composite material and its derivative materials prepared by the preparation method of the present invention can be used as a flexible composite electrode, and can exhibit excellent electrochemical stability even in a bent state; (3) The MXene / two-dimensional conductive MOF composite material and its derivative materials prepared by the preparation method of the present invention retain the original structure of MXene and C-MOF, and have the excellent properties of both. The supercapacitor performance of flexible supercapacitors used as flexible electrodes is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Shown is the two-dimensional Ti3C2T prepared in Example 1 x @TEM image of Fe3(HITP)2 derivative.

[0027] Figure 2 The two-dimensional Ti3C2T prepared in Example 1 and Comparative Examples 1 to 3 are shown. x @Fe3(HITP)2 derivatives, Fe3(HITP)2, Ti3C2T x 、Ti3C2T x Raman image of @Fe3(HITP)2.

[0028] Figure 3 The two-dimensional Ti3C2T prepared in Example 1, Comparative Examples 2 and 3 are shown. x @Fe3(HITP)2 derivatives, Ti3C2T x 、Ti3C2T x The three-electrode system with Fe3(HITP)2 as the working electrode at 5mV s -1 Cyclic voltammetry curve image at different scan rates. DETAILED DESCRIPTION

[0029] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0030] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0031] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0032] Example 1 This embodiment provides a method for preparing a MXene / two-dimensional conductive MOF composite material, comprising the following steps: (1) Add 1 g LiF solid and 10 mL HCl (9 M) to a centrifuge tube, stir and react at 35 °C for 10 min, then add 1 g Ti3Al2C2 solid and continue heating and reacting for 24 h. After the reaction is completed, wash with deionized water until the pH reaches 6-7. x The solid was dispersed with deionized water and ultrasonicated for 1 h under nitrogen flow. The upper dispersion was centrifuged at 3500 rpm for 10 min to obtain the monolayer Ti3C2T x Colloidal solutions; (2) Add 6 mL of deionized water, 2 mL of HATP dispersion (0.5 mg / mL), and 6 mL of single-layer Ti3C2T x Dispersion liquid (5 mg / mL), 1 mL FeCl3 dispersion liquid (0.5 mg / mL), and 0.45 mL ammonia water (14 M) were stirred and reacted at room temperature for 2 h, and then the MXene@Fe3(HITP)2 mixed liquid was vacuum filtered through a nanoporous membrane and washed with 10 mL deionized water solution. After filtration, it was dried in a vacuum oven at 60 ° C for 1 h to obtain MXene@Fe3(HITP)2, which is a MXene / two-dimensional conductive MOF composite material.

[0033] The present embodiment provides a method for preparing a derivative material of the above-mentioned MXene / two-dimensional conductive MOF composite material, comprising the following steps: heating the above-mentioned MXene@Fe3(HITP)2 to 350°C at a rate of 10°C / min under the condition of passing argon gas in a tube furnace, keeping the temperature at 350°C for 1h and then cooling to room temperature to obtain Ti3C2T x@Fe3(HITP)2 derivatives are derivative materials of MXene / two-dimensional conductive MOF composite materials.

[0034] For the two-dimensional Ti3C2T x The morphology of the samples of @Fe3(HITP)2 derivatives was characterized and analyzed. The test results are as follows Figure 1 As shown, from Figure 1 It can be seen that the obtained Ti3C2T x @Fe3(HITP)2 derivative composite film is stacked in the form of nanosheets.

[0035] Example 2 This embodiment provides a method for preparing a MXene / two-dimensional conductive MOF composite material, comprising the following steps: (1) Add 1.5 g LiF solid and 20 mL HCl (9 M) to a centrifuge tube, stir and react at 35 °C for 10 min, then add 1 g V2AlC solid and continue heating and reacting for 10 h. After the reaction is completed, wash with deionized water until the pH reaches 6-7. x The solid was dispersed with deionized water and ultrasonicated for 2 h under argon gas. The upper dispersion was centrifuged at 3500 rpm for 10 min and the monolayer V2CT was obtained. x Colloidal solutions; (2) Add 8 mL of deionized water, 4 mL of HATP dispersion (0.5 mg / mL), and 16 mL of single-layer V2CT to a 50 mL glass bottle. x Dispersion (2 mg / mL), 2 mL FeCl3 dispersion (0.6 mg / mL), 0.9 mL ammonia (14 M), stirred at room temperature for 2 h, and then filtered through a nanoporous membrane V2CT vacuum filter x @Fe3(HITP)2 mixed solution, and washed with 10mL deionized water solution, and dried in a vacuum oven at 60℃ for 2h to obtain V2CT x @Fe3(HITP)2, which is a MXene / two-dimensional conductive MOF composite material.

[0036] This embodiment provides a method for preparing a derivative material of the above MXene / two-dimensional conductive MOF composite material, comprising the following steps: x @Fe3(HITP)2 was heated to 250℃ at a rate of 10℃ / min in a tube furnace under the condition of nitrogen gas, and kept at 250℃ for 2h and then cooled to room temperature to obtain V2CT x @Fe3(HITP)2 derivatives are derivative materials of MXene / two-dimensional conductive MOF composite materials.

[0037] Example 3 This embodiment provides a method for preparing a MXene / two-dimensional conductive MOF composite material, comprising the following steps: (1) Add 1 g LiF solid and 20 mL HCl (9 M) to a centrifuge tube, stir and react at 35 °C for 10 min, then add 1 g Ti3Al2C2 solid and continue heating and reacting for 48 h. After the reaction is completed, wash with deionized water until the pH reaches 6-7. x The solid was dispersed with deionized water and ultrasonicated for 3 h under nitrogen flow. The upper dispersion was centrifuged at 3500 rpm for 10 min to obtain the monolayer Ti3C2T x Colloidal solutions; (2) Add 8 mL of deionized water, 1 mL of HATP dispersion (1 mg / mL), and 10 mL of single-layer Ti3C2T x The Ti3C2T dispersion (3 mg / mL), 1 mL CuCl2 dispersion (0.5 mg / mL), and 0.6 mL ammonia (14 M) were stirred at room temperature for 6 h and then vacuum filtered through a nanoporous membrane. x @Cu3(HITP)2 mixed solution, and washed with 10mL deionized water solution. After filtration, it was dried in a vacuum oven at 60℃ for 2h to obtain Ti3C2T x @Cu3(HITP)2, which is a MXene / two-dimensional conductive MOF composite material.

[0038] This embodiment provides a method for preparing a derivative material of the above-mentioned MXene / two-dimensional conductive MOF composite material, comprising the following steps: x @Cu3(HITP)2 was heated to 450°C at a rate of 10°C / min in a tubular furnace under the condition of passing nitrogen, and kept at 450°C for 0.5h and then cooled to room temperature to obtain a MXene@Cu3(HITP)2 derivative, which is a derivative material of the MXene / two-dimensional conductive MOF composite material.

[0039] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that only step (2) is performed and Ti3C2T is not added to the reaction solution. x , the other process conditions are exactly the same.

[0040] In a 50 mL glass bottle, add 12 mL of deionized water, 2 mL of HATP dispersion (5 mg / mL), 1 mL of FeCl3 dispersion (5 mg / mL), and 0.45 mL of ammonia water (14 M). After stirring at room temperature for 2 h, wash with deionized water solution, and dry in a vacuum oven at 60 ° C for 12 h to obtain Fe3(HITP)2 powder.

[0041] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that only step (1) is carried out in the reaction step, and the other process conditions are exactly the same.

[0042] Single layer Ti3C2T x Preparation of colloidal solution: Add 1g LiF solid and 10mL HCl (9M) into a centrifuge tube, stir and react at 35℃ for 10min, then add 1g Ti3Al2C2 solid and continue heating and reacting for 24h. After the reaction, wash with deionized water until the pH reaches 6-7. x The solid was dispersed with deionized water and ultrasonicated for 1 h under nitrogen flow. The upper dispersion was centrifuged at 3500 rpm for 10 min to obtain the monolayer Ti3C2T x Colloidal solution.

[0043] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that only step (1) and step (2) are carried out in the reaction steps, and the other process conditions are exactly the same.

[0044] (1) Add 1 g LiF solid and 10 mL HCl (9 M) to a centrifuge tube, stir and react at 35 °C for 10 min, then add 1 g Ti3Al2C2 solid and continue heating and reacting for 24 h. After the reaction is completed, wash with deionized water until the pH reaches 6-7. x The solid was dispersed with deionized water and ultrasonicated for 1 h under nitrogen flow. The upper dispersion was centrifuged at 3500 rpm for 10 min to obtain the monolayer Ti3C2T x Colloidal solutions; (2) Add 6 mL of deionized water, 2 mL of HATP dispersion (0.5 mg / mL), and 6 mL of single-layer Ti3C2T x Dispersion liquid (5 mg / mL), 1 mL FeCl3 dispersion liquid (0.5 mg / mL), and 0.45 mL ammonia water (14 M) were stirred and reacted at room temperature for 2 h. The MXene@Fe3(HITP)2 mixture was vacuum filtered through a nanoporous membrane and washed with 10 mL deionized water. After filtration, it was dried in a vacuum oven at 60 °C for 1 h to obtain MXene@Fe3(HITP)2.

[0045] The derived materials of the MXene / two-dimensional conductive MOF composite material prepared in Example 1 and the materials prepared in Comparative Examples 1 to 3 were characterized by Raman spectroscopy. The results are as follows: Figure 2 As shown, from Figure 2 It can be seen that Ti3C2T xThe nanosheets have a wavelength of 278, 392, and 606 cm −1 Peaks appeared at , corresponding to the typical E g Group vibration and in-plane vibration mode. Since Fe3(HITP)2 has a graphene-like π-d conjugated structure, pure Fe3(HITP)2 has D and G peaks. x @Fe3(HITP)2 and Ti3C2T x @Fe3(HITP)2 derivative films show gradually enhanced D and G peaks and E g The group vibration peaks indicate that Fe3(HITP)2 is successfully composited with MXene as an intercalation agent.

[0046] The derivative material of the MXene / two-dimensional conductive MOF composite material prepared in Example 1 and the materials prepared in Comparative Examples 2 and 3 were used as working electrodes, silver chloride was used as a reference electrode, and a graphite rod was used as a counter electrode in a three-electrode system at 5 mVs -1 The cyclic voltammetry curve at the scan rate is as follows Figure 3 As shown, from Figure 3 It can be seen that Ti3C2T x The capacitance of MXene@Fe3(HITP)2 and MXene@Fe3(HITP)2 derivatives increases in turn. Example 1 uses the best reaction parameters, so the obtained two-dimensional Ti3C2Tx@Fe3(HITP)2 and its derivatives have the best performance as flexible composite electrodes in supercapacitors.

[0047] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a MXene / two-dimensional conductive MOF composite material, characterized in that: A reaction solution containing a single layer of MXene, metal ions, ligands and an initiator is reacted to obtain a MXene / two-dimensional conductive MOF composite material.

2. The preparation method according to claim 1, characterized in that: The metal ion is selected from Ni 2+ , Cu 2+ and Fe 3+ One or more of .

3. The preparation method according to claim 1, characterized in that: The ligand is selected from one or more of 1,2,4,5-tetraaminobenzene tetrahydrochloride, 2,3,6,7,10,11-hexaaminotriphenyl hexahydrochloride and 2,3,6,7,10,11-hexahydroxytriphenyl; the initiator is ammonia water, and the volume ratio of ammonia water to the reaction solution is (1-5):(50-500).

4. The preparation method according to claim 1, characterized in that: The metal ions are added in the form of soluble metal salts, and the mass ratio of the monolayer MXene, the ligand and the soluble metal salt is (10-50):(0.5-10):(0.5-10).

5. A MXene / two-dimensional conductive MOF composite material prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the MXene / two-dimensional conductive MOF composite material according to claim 5 as a flexible electrode in a flexible supercapacitor.

7. A method for preparing a derivative material of a MXene / two-dimensional conductive MOF composite material, characterized in that: The MXene / two-dimensional conductive MOF composite material as claimed in claim 5 is annealed under a protective atmosphere to obtain a derivative material of the MXene / two-dimensional conductive MOF composite material.

8. The preparation method according to claim 7, characterized in that: The annealing temperature is 100~600℃, and the annealing time is 0.5~6h.

9. A derivative material of the MXene / two-dimensional conductive MOF composite material prepared by the preparation method according to claim 7 or 8.

10. Use of the MXene / two-dimensional conductive MOF composite material according to claim 9 as a flexible electrode in a flexible supercapacitor.

Citation Information

Patent Citations

  • MXene material and preparation method and application thereof

    CN106430195A

  • In-situ preparation method of three-dimensional conductive MOF@MXene composite electrode

    CN112053861A

  • MOF-coated MXene composite structure electrode material for super capacitor and preparation method of MOF-coated MXene composite structure electrode material

    CN117253725A

  • MXene-coated NiCo-MOF composite material and preparation and application thereof

    CN118919307A

  • MXene-DERIVED METAL-ORGANIC FRAMEWORKS AND METHOD

    US20220387970A1

Cited By

  • Fluorinated modified MXene-based conductive composite material and preparation method thereof

    CN121948451A